Comic Media in Learning of Elementary Schools: Systematic Literature Review - Puspitasari, Wina Dwi; Rodiyana, Roni (Journal of Innovation and Research in Primary Education, 2022)
Comics are alternative media that can be used by teachers in carrying out learning in elementary schools. Learning comics are stories made by teachers with certain characters with the aim of making it easier for students to understand the material. This research using the concept of literature review uses the Systematic Literature Review (SLR) technique. The Systematic Literature Review technique is carried out by reviewing articles that are in accordance with the topic of the research question and then making an in-depth study of the articles that have been reviewed. The results of the data analysis that has been carried out are that the use of comics can improve students' understanding of the material which results in improving student learning outcomes in elementary schools. In addition, the cultivation of good character values can be done through the use of comics. Another result is that the local culture of the local area in the elementary school can be used as a good alternative in setting up comic stories. It is necessary to choose a good topic so that the comics used can make it easier for students to understand the material.